2023
DOI: 10.1002/bco2.208
|View full text |Cite
|
Sign up to set email alerts
|

Robotic‐assisted versus laparoscopic nephroureterectomy; a systematic review and meta‐analysis

Abstract: Background: Upper tract urothelial carcinoma (UTUC) is the malignant transformation of urothelial cells, from the renal calyces to the ureteral orifices. While the benefits of minimally invasive nephroureterectomy over their open counterpart have been established, the optimal technique remains a debate. We aimed to assess current evidence in the literature and compare outcomes between robotic-assisted (RANU) and laparoscopic nephroureterectomy (LNU).Methods: A systematic review of the literature was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
3
1
Order By: Relevance
“…Finally, our study mortality rate at 24 months is 3% (2/66) patients. Our rate is higher than what has been reported by others (20). However, it is of note that our data relies on a real-life cohort and that the large con dence interval is not suited for comparability.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Finally, our study mortality rate at 24 months is 3% (2/66) patients. Our rate is higher than what has been reported by others (20). However, it is of note that our data relies on a real-life cohort and that the large con dence interval is not suited for comparability.…”
Section: Discussioncontrasting
confidence: 73%
“…For example, the multicenter study by Campi et al relied on a total combined cohort of 81, with a highly variable robotic caseload (19). Moreover, similar to RARC patients UTUC patients represent a highly variable patient cohort, young and t patients vs. senior patients with high comorbidity burden and previous surgical interventions (20). Thus, we relied on a real world cohort without strict selection criteria with an adequate sample size and a single robotic-surgeon expert with a combined caseload of over 2000 combined robotic procedures (i.e RARP, RARCs and complete or partial nephrectomies).…”
Section: Discussionmentioning
confidence: 99%
“…Since the first report in 2006 ( 15 ) and subsequent studies introducing technical refinements ( 16 - 20 ), RANU has been increasingly adopted in real-world clinical practice. As a result, several studies have reported the advantages of RANU over other surgical approaches ( 21 - 23 ). Veccia et al performed a systematic review and meta-analysis and reported that RANU could offer benefits as a minimally invasive approach without impairing oncological outcomes compared to open and laparoscopic nephroureterectomies ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Veccia et al performed a systematic review and meta-analysis and reported that RANU could offer benefits as a minimally invasive approach without impairing oncological outcomes compared to open and laparoscopic nephroureterectomies ( 21 ). However, accumulating findings with respect to RANU are still limited to studies performed with da Vinci ( 15 - 23 ). The present study summarizes the perioperative findings of the first series of eight patients undergoing RANU using hinotori.…”
Section: Discussionmentioning
confidence: 99%